TRADITIONAL AND MODERN MUSLIM EDUCATION IN THE CENTER AND PERIPHERY: ONGOING CHALLENGES - Moch Faisal; Wasehudin; Erdi Rudjikartawi; Agus Gunawan; Elis Haerani (Cakrawala Pedagogik, 2025)
Traditional and modern Muslim education in the core and periphery: enduring challenges. This study aims to identify the interaction between traditional and modern education in the context of Muslim education, exploring the challenges faced by Muslim education in marginalized areas in achieving access to quality education. It analyzes the role of government and educational institutions in addressing the gap between traditional and modern education, and explores best practices from countries with large Muslim populations for adaptation to local contexts. The study examines case studies, and document analysis from various sources. The study discusses various challenges faced by Muslim education, both at the traditional and modern levels. Integration of both educational approaches, development of relevant curricula, improvement of teacher quality, and support from the government and community are proposed solutions to address these challenges. Through these efforts, it is hoped that Muslim education can produce a generation of quality and able to compete globally.